Intellectual Property Rights in the Age of AI and Big Data: A Reinterpretation of the Concept of Creativity in Legal Philosophy - Pranajaya, I Kadek Widi; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
The legal issue addressed is the growing misalignment between traditional IPR doctrines—which require originality and human subjectivity—and the emerging reality of content creation that is either generated or significantly assisted by AI systems and data-driven processes. The primary objective of this research is to critically reassess the normative foundations of the concept of